Difference between revisions of "009B Sample Final 1, Problem 4"

From Math Wiki
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
 
<span class="exam"> Compute the following integrals.
 
<span class="exam"> Compute the following integrals.
  
::<span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math>
+
<span class="exam">(a) &nbsp;<math>\int \frac{t^2}{\sqrt{1-t^6}}~dt</math>
  
::<span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math>
+
<span class="exam">(b) &nbsp;<math>\int \frac{2x^2+1}{2x^2+x}~dx</math>
  
::<span class="exam">c) <math>\int \sin^3x~dx</math>
+
<span class="exam">(c) &nbsp;<math>\int \sin^3x~dx</math>
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|Recall:
+
|'''1.''' Through partial fraction decomposition, we can write the fraction
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math>
::'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math>
 
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;for some constants <math style="vertical-align: -4px">A,B.</math>
::'''2.''' Through partial fraction decomposition, we can write the fraction &nbsp;<math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> &nbsp;
 
 
|-
 
|-
|
+
|'''2.''' Recall the Pythagorean identity
:::for some constants <math style="vertical-align: -4px">A,B.</math>
 
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">\sin^2(x)+\cos^2(x)=1.</math>
::'''3.''' We have the Pythagorean identity <math style="vertical-align: -5px">\sin^2(x)=1-\cos^2(x).</math>
 
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 32: Line 29:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We first distribute to get
+
|We first note that
 
|-
 
|-
 
|
 
|
::<math>\int e^x(x+\sin(e^x))~dx\,=\,\int e^xx~dx+\int e^x\sin(e^x)~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\int \frac{t^2}{\sqrt{1-t^6}}~dt=\int \frac{t^2}{\sqrt{1-(t^3)^2}}~dt.</math>
 +
|-
 +
|Now, we proceed by &nbsp;<math>u</math>-substitution. 
 
|-
 
|-
|Now, for the first integral on the right hand side of the last equation, we use integration by parts.  
+
|Let &nbsp;<math style="vertical-align: 0px">u=t^3.</math> &nbsp;
 
|-
 
|-
|Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
+
|Then, &nbsp; <math style="vertical-align: 0px">du=3t^2dt</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{3}=t^2dt.</math>
 
|-
 
|-
 
|So, we have
 
|So, we have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\int \frac{t^2}{\sqrt{1-t^6}}~dt=\int \frac{1}{3\sqrt{1-u^2}}~du.</math>
\displaystyle{\int e^x(x+\sin(e^x))~dx} & = & \displaystyle{\bigg(xe^x-\int e^x~dx \bigg)+\int e^x\sin(e^x)~dx}\\
 
&&\\
 
& = & \displaystyle{xe^x-e^x+\int e^x\sin(e^x)~dx}.\\
 
\end{array}</math>
 
 
|}
 
|}
  
Line 54: Line 49:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, for the one remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
+
|Now, we need to use trig substitution.
 
|-
 
|-
|Let <math style="vertical-align: 0px">u=e^x.</math> Then, <math style="vertical-align: 0px">du=e^xdx.</math>  
+
|Let &nbsp;<math style="vertical-align: -1px">u=\sin \theta.</math>&nbsp; Then, &nbsp;<math style="vertical-align: 0px">du=\cos \theta d\theta.</math>
 
|-
 
|-
 
|So, we have
 
|So, we have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
\displaystyle{\int e^x(x+\sin(e^x))~dx} & = & \displaystyle{xe^x-e^x+\int \sin(u)~du}\\
+
\displaystyle{\int \frac{t^2}{\sqrt{1-t^6}}~dt} & = & \displaystyle{\int \frac{\cos \theta}{3\sqrt{1-\sin^2\theta}}~d\theta}\\
 +
&&\\
 +
& = & \displaystyle{\int \frac{\cos \theta}{3\sqrt{\cos^2\theta}}~d\theta}\\
 +
&&\\
 +
& = & \displaystyle{\int \frac{\cos \theta}{3\cos \theta} d\theta}\\
 +
&&\\
 +
& = & \displaystyle{\int \frac{1}{3}~d\theta}\\
 +
&&\\
 +
& = & \displaystyle{\frac{1}{3}\theta +C}\\
 
&&\\
 
&&\\
& = & \displaystyle{xe^x-e^x-\cos(u)+C}\\
+
& = & \displaystyle{\frac{1}{3}\arcsin(u)+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{xe^x-e^x-\cos(e^x)+C}.\\
+
& = & \displaystyle{\frac{1}{3}\arcsin(t^3)+C.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 75: Line 78:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we add and subtract <math style="vertical-align: 0px">x</math> from the numerator.  
+
|First, we add and subtract &nbsp;<math style="vertical-align: 0px">x</math>&nbsp; from the numerator.  
 
|-
 
|-
 
|So, we have
 
|So, we have
Line 85: Line 88:
 
& = & \displaystyle{\int \frac{2x^2+x}{2x^2+x}~dx+\int\frac{1-x}{2x^2+x}~dx}\\
 
& = & \displaystyle{\int \frac{2x^2+x}{2x^2+x}~dx+\int\frac{1-x}{2x^2+x}~dx}\\
 
&&\\
 
&&\\
& = & \displaystyle{\int ~dx+\int\frac{1-x}{2x^2+x}~dx}.\\
+
& = & \displaystyle{\int 1~dx+\int\frac{1-x}{2x^2+x}~dx}.\\
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 94: Line 97:
 
|Now, we need to use partial fraction decomposition for the second integral.
 
|Now, we need to use partial fraction decomposition for the second integral.
 
|-
 
|-
|Since <math style="vertical-align: -5px">2x^2+x=x(2x+1),</math> we let  
+
|Since &nbsp;<math style="vertical-align: -5px">2x^2+x=x(2x+1),</math>&nbsp; we let  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}.</math>
::<math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}.</math>
 
 
|-
 
|-
|Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1),</math> we get
+
|Multiplying both sides of the last equation by &nbsp;<math style="vertical-align: -5px">x(2x+1),</math>
 
|-
 
|-
|
+
|we get
::<math style="vertical-align: -5px">1-x=A(2x+1)+Bx.</math>
 
 
|-
 
|-
|If we let <math style="vertical-align: 0px">x=0</math>, the last equation becomes
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">1-x=A(2x+1)+Bx.</math>
 
|-
 
|-
|
+
|If we let &nbsp;<math style="vertical-align: -5px">x=0,</math> the last equation becomes &nbsp;<math style="vertical-align: -1px">1=A.</math>
::<math style="vertical-align: -1px">1=A.</math>
 
|-
 
|If we let <math style="vertical-align: -14px">x=-\frac{1}{2},</math> then we get &thinsp;<math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B.</math> Thus,
 
 
|-
 
|-
|
+
|If we let &nbsp;<math style="vertical-align: -14px">x=-\frac{1}{2},</math>&nbsp; then we get &nbsp;<math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B.</math>&nbsp; Thus, &nbsp;<math style="vertical-align: 0px">B=-3.</math>
::<math style="vertical-align: 0px">B=-3.</math>
 
 
|-
 
|-
|So, in summation, we have&thinsp;
+
|So, in summation, we have  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}.</math>
::<math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}.</math>
 
 
|}
 
|}
  
Line 126: Line 122:
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{\int ~dx+\int\frac{1}{x}~dx+\int\frac{-3}{2x+1}~dx}\\
+
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{\int 1~dx+\int\frac{1}{x}~dx+\int\frac{-3}{2x+1}~dx}\\
 
&&\\
 
&&\\
& = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx}.\\
+
& = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx.}\\
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 136: Line 132:
 
!Step 4: &nbsp;
 
!Step 4: &nbsp;
 
|-
 
|-
|For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
+
|For the final remaining integral, we use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -2px">u=2x+1.</math>&nbsp;
 
|-
 
|-
|Let <math style="vertical-align: -2px">u=2x+1.</math> Then, <math style="vertical-align: 0px">du=2\,dx</math> and&thinsp; <math style="vertical-align: -14px">\frac{du}{2}=dx.</math>
+
|Then, &nbsp;<math style="vertical-align: 0px">du=2\,dx</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{2}=dx.</math>
 
|-
 
|-
|Thus, our final integral becomes
+
|Thus, our integral becomes
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx}\\
 
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{x+\ln x+\int\frac{-3}{2u}~du}\\
 
& = & \displaystyle{x+\ln x+\int\frac{-3}{2u}~du}\\
 
&&\\
 
&&\\
& = & \displaystyle{x+\ln x-\frac{3}{2}\ln u +C}.\\
+
& = & \displaystyle{x+\ln x-\frac{3}{2}\ln u +C.}\\
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
Line 154: Line 152:
 
|-
 
|-
 
|
 
|
::<math>\int \frac{2x^2+1}{2x^2+x}~dx\,=\,x+\ln x-\frac{3}{2}\ln (2x+1) +C.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 +
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x-\frac{3}{2}\ln (2x+1) +C.}
 +
\end{array}</math>
 
|}
 
|}
  
Line 162: Line 162:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we write <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx.</math>
+
|First, we write  
 
|-
 
|-
|Using the identity <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math>, we get
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx.</math>
 
|-
 
|-
|
+
|Using the identity &nbsp;<math style="vertical-align: -5px">\sin^2x+\cos^2x=1,</math>&nbsp; we get
::<math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math>  
+
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math>  
 
|-
 
|-
 
|If we use this identity, we have
 
|If we use this identity, we have
 
|-
 
|-
| &nbsp; &nbsp; <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math>
 +
|-
 +
|
 
|}
 
|}
  
Line 177: Line 180:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x dx.</math>  
+
|Now, we proceed by &nbsp;<math>u</math>-substitution.  
 +
|-
 +
|Let &nbsp;<math>u=\cos x.</math>&nbsp; Then, &nbsp;<math style="vertical-align: -1px">du=-\sin x dx.</math>  
 
|-
 
|-
 
|So we have
 
|So we have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int\sin^3x~dx} & = & \displaystyle{\int -(1-u^2)~du}\\
 
\displaystyle{\int\sin^3x~dx} & = & \displaystyle{\int -(1-u^2)~du}\\
 
&&\\
 
&&\\
Line 192: Line 197:
 
|
 
|
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; '''(a)''' &nbsp;<math>xe^x-e^x-\cos(e^x)+C</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp;<math>\frac{1}{3}\arcsin(t^3)+C</math>
 
|-
 
|-
|&nbsp;&nbsp; '''(b)''' &nbsp;<math style="vertical-align: -14px">x+\ln x-\frac{3}{2}\ln (2x+1) +C</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp;<math style="vertical-align: -14px">x+\ln x-\frac{3}{2}\ln (2x+1) +C</math>
 
|-
 
|-
|&nbsp;&nbsp; '''(c)''' &nbsp;<math style="vertical-align: -14px">-\cos x+\frac{\cos^3x}{3}+C</math>
+
|&nbsp; &nbsp; '''(c)''' &nbsp; &nbsp;<math style="vertical-align: -14px">-\cos x+\frac{\cos^3x}{3}+C</math>
 
|}
 
|}
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:05, 20 May 2017

Compute the following integrals.

(a)  

(b)  

(c)  

Foundations:  
1. Through partial fraction decomposition, we can write the fraction
       
       for some constants
2. Recall the Pythagorean identity
       


Solution:

(a)

Step 1:  
We first note that

       

Now, we proceed by  -substitution.
Let    
Then,     and  
So, we have

       

Step 2:  
Now, we need to use trig substitution.
Let    Then,  
So, we have

       

(b)

Step 1:  
First, we add and subtract    from the numerator.
So, we have
Step 2:  
Now, we need to use partial fraction decomposition for the second integral.
Since    we let
       
Multiplying both sides of the last equation by  
we get
       
If we let   the last equation becomes  
If we let    then we get    Thus,  
So, in summation, we have
       
Step 3:  
If we plug in the last equation from Step 2 into our final integral in Step 1, we have

       

Step 4:  
For the final remaining integral, we use  -substitution.
Let   
Then,    and  
Thus, our integral becomes

       

Therefore, the final answer is

       

(c)

Step 1:  
First, we write
       
Using the identity    we get
       
If we use this identity, we have
       
Step 2:  
Now, we proceed by  -substitution.
Let    Then,  
So we have

       


Final Answer:  
    (a)    
    (b)    
    (c)    

Return to Sample Exam